2016
DOI: 10.1016/j.ijcard.2016.08.250
|View full text |Cite
|
Sign up to set email alerts
|

On- vs. off-pump coronary artery bypass grafting: A systematic review and meta-analysis

Abstract: Off-pump CABG has some benefits over on-pump CABG, particularly in relation to post-operative atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 70 publications
(55 reference statements)
2
40
3
3
Order By: Relevance
“…Previous studies have shown no difference in short‐term (30‐day) mortality between off‐pump beating and on‐pump coronary artery bypass grafting (CABG) . Off‐pump CABG may reduce the incidence of postoperative stroke, renal dysfunction, mediastinitis, and atrial fibrillation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown no difference in short‐term (30‐day) mortality between off‐pump beating and on‐pump coronary artery bypass grafting (CABG) . Off‐pump CABG may reduce the incidence of postoperative stroke, renal dysfunction, mediastinitis, and atrial fibrillation .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown no difference in short‐term (30‐day) mortality between off‐pump beating and on‐pump coronary artery bypass grafting (CABG) . Off‐pump CABG may reduce the incidence of postoperative stroke, renal dysfunction, mediastinitis, and atrial fibrillation . Off‐pump CABG has also been associated with a reduction in the length of ventilation and intensive care unit and hospital stay, less transfusion requirements, and less chest tube drainage .…”
Section: Introductionmentioning
confidence: 99%
“…Patients after off-pump coronary artery bypass grafting (OPCAB) are usually easier to wean, and they have less postoperative respiratory complications in comparison with on-pump surgery (11, 12). However, the number of patients operated with OPCAB technique reaches 60–100% in some regions (13) leading to increased load on the personnel of cardiosurgical ICU.…”
Section: Introductionmentioning
confidence: 99%
“…The role of INTELLiVENT-ASV mode during weaning from ventilation after OPCAB is still unsettled. Thus, it is important to assess efficacy and safety of the automated weaning mode in the off-pump coronary patients (12). …”
Section: Introductionmentioning
confidence: 99%
“…Deppe et al also found a reduced incidence of stroke in the off pump group, whilst this group also had an increased need for revascularisation (4). The latest metaanalysis by Dieberg et al reported a P value of 0.05 for the stroke comparison and only found a significant difference in the incidence of atrial fibrillation (7). Two limitations that affect each of these studies are the small size of many of the included RCTs and a concentration on short term (30 days) outcomes (4-7).…”
mentioning
confidence: 99%